Inflammatory index score in children: its relationship with neophobia, dietary quality and anthropometric measurements - Didem Kanısoy; Seray Kabaran (BMC, 2024)
Abstract The aim of this study was to examine the correlation between the Diet Inflammatory Index (DII) scores and dietary quality in children, which was measured by the Mediterranean Diet Quality Index (KIDMED), also neophobia scores and anthropometric measurements. This study was conducted in primary schools in Famagusta, Cyprus. A total of 300 children (150 girls, 150 boys) in the 3rd, 4th and 5th grade were included in the study. The frequency of food consumption was measured to calculate the DII scores. Moreover, neophobia and KIDMED scores were obtained. The KIDMED score is a popular tool that is mostly used as a practical scale to assess adherence to the Mediterranean diet among children. Additionally, anthropometric measurements (body weight, height, waist circumference, neck circumference) were collected. Finally, DII scores were compared with KIDMED scores, neophobia scores, and anthropometric measurements. Anthropometric measurements and body mass index (BMI) values were found to be significantly different (p < 0.05) based on the DII scores. Children with DII scores in the 1st quartile had significantly different anthropometric measurements compared to those who had scores in the 2nd, 3rd, and 4th quartiles (p < 0.05). The DII scores of normal-weight children were higher than those of obese children. A significant negative correlation was observed between KIDMED scores and DII scores of the children (p < 0.05). Furthermore, a significant positive correlation was observed between neophobia scores and DII scores (p < 0.05). Additionally, DII scores were correlated with dietary quality and anthropometric measurements (p < 0.05). The MD enhances the anti-inflammatory properties of the diet; it has clearly demonstrated positive effects on diet quality and anthropometric measurements. Furthermore, the MD is suggested to reduce the risk of chronic diseases as a result of improving DII scores at an early age.